Charles Follen McKim papers - McKim, Charles Follen, 1847-1909.
Correspondence, letterbooks, memoranda, diary transcript, notes, legal and financial records, sketches, drawings, photographs, and other papers relating chiefly to the firm of McKim, Mead, & White, New York, N.Y. Documents McKim's designs for the Boston Public Library and Symphony Hall, Boston, Mass.; Columbia University's Morningside Heights campus and the University Club, New York, N.Y.; Rhode Island State House, Providence, R.I.; restoration of the White House, Washington, D.C.; and the World's Columbian Exposition, Chicago,Ill, 1893. Also documents McKim's work on the U.S. Senate Commission for the Improvement of the District of Columbia concerned with the location and treatment of public buildings and grounds along the Mall and his membership on the Grant Memorial Commission. Includes material pertaining to McKim's membership in societies and clubs including the American Institute of Architects, the Century Club, and the University Club. Subjects include the development of American architecture, establishment of the American Academy in Rome, and efforts of abolitionists to provide aid for newly freed slaves in the years following the Civil War. Diary includes McKim's account of an 1863 walking tour with Francis Jackson Garrison and Wendell Phillips Garrison to the Gettysburg battlefield and other areas in eastern Pennsylvania.
Family correspondents include McKim's daughter, Margaret McKim; his father, J. Miller M'Kim; and other family members. Other correspondents include Daniel Chester French, John La Farge, Francis Jackson Garrison, Wendell Phillips Garrison, William Lloyd Garrison, Francis Davis Millet, Charles Moore, H. Siddons Mowbray, Frederick Law Olmsted, and Augustus Saint-Gaudens.
Microfilm edition available
Microfilm edition produced from originals in Manuscript Division.
In part, transcripts.
Architect.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: French, Daniel Chester, -- 1850-1931 -- Correspondence; Garrison, Francis Jackson, -- 1848-1916.; Garrison, Francis Jackson, -- 1848-1916 -- Correspondence; Garrison, William Lloyd, -- 1805-1879 -- Correspondence; Garrison, Wendell Phillips, -- 1840-1907.; Garrison, Wendell Phillips, -- 1840-1907 -- Correspondence; La Farge, John, -- 1835-1910 -- Correspondence; Millet, Francis Davis, -- 1846-1912 -- Correspondence; M'Kim, J. Miller -- 1810-1874 -- Correspondence; McKim, Margaret -- Correspondence; Moore, Charles, -- 1855-1942 -- Correspondence; Mowbray, H. Siddons -- 1858-1928 -- Correspondence; Olmsted, Frederick Law, -- 1822-1903 -- Correspondence; Saint-Gaudens, Augustus, -- 1848-1907 -- Correspondence; McKim family -- Correspondence; United States. -- Congress. -- Senate. -- Commission for the Improvement of the District of Columbia; American Academy in Rome; American Institute of Architects; Boston Public Library; Century Club (New York, N.Y.); Columbia University; Grant Memorial Commission; McKim, Mead, & White; Rhode Island State House (Providence, R.I.); Symphony Hall (Boston, Mass.); University Club (New York, N.Y.); White House (Washington, D.C.); African Americans -- History -- 19th century; Architectural firms -- New York (State) -- New York; Architecture -- Societies, etc; Architecture -- Study and teaching -- Italy -- Rome; Architecture -- Massachusetts -- Boston; Architecture -- New York (State) -- New York; Architecture -- Conservation and restoration -- Washington (D.C.); Architecture -- United States; Architecture -- Washington (D.C.); Clubs -- New York (State) -- New York; Exhibitions -- Illinois -- Chicago; Freedmen; Libraries -- Massachusetts -- Boston; Music-halls -- Massachusetts -- Boston; Parks -- Washington (D.C.); Public buildings -- Washington (D.C.); Reconstruction (U.S. history, 1865-1877); Universities and colleges -- New York (State) -- New York; Mall, The (Washington, D.C.); Gettysburg (Pa.) -- History -- Civil War, 1861-1865; Pennsylvania -- Description and travel; Rhode Island -- Capital and capitol; Architects